Prediction of atrial fibrillation development and progression: Current perspectives - Vlachos, Konstantinos (World J Cardiol, 2016)
Atrial fibrillation (AF) is the most common arrhythmia in clinical practice. Several conventional and novel predictors of AF development and progression (from paroxysmal to persistent and permanent types) have been reported. The most important predictor of AF progression is possibly the arrhythmia itself. The electrical, mechanical and structural remodeling determines the perpetuation of AF and the progression from paroxysmal to persistent and permanent forms. Common clinical scores such as the hypertension, age ≥ 75 years, transient ischemic attack or stroke, chronic obstructive pulmonary disease, and heart failure and the congestive heart failure, hypertension, age ≥ 75 years, diabetes mellitus, stroke/transient ischemic attack, vascular disease, age 65-74 years, sex category scores as well as biomarkers related to inflammation may also add important information on this topic. There is now increasing evidence that even in patients with so-called lone or idiopathic AF, the arrhythmia is the manifestation of a structural atrial disease which has recently been defined and described as fibrotic atrial cardiomyopathy. Fibrosis results from a broad range of factors related to AF inducing pathologies such as cell stretch, neurohumoral activation, and oxidative stress. The extent of fibrosis as detected either by late gadolinium enhancement-magnetic resonance imaging or electroanatomic voltage mapping may guide the therapeutic approach based on the arrhythmia substrate. The knowledge of these risk factors may not only delay arrhythmia progression, but also reduce the arrhythmia burden in patients with first detected AF. The present review highlights on the conventional and novel risk factors of development and progression of AF.